FIFTH-GRADE STUDENTS’ CREATIVITY IN WRITING THREE-PARAGRAPH SHORT STORIES AT SDN 1 SELAJAMBE - Anita,; Helmanto, Fachri; Efendi, Irwan (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Primary education plays a vital role in cultivating students’ creativity by fostering exploration, experimentation, imagination, and critical thinking. However, structured practices in writing three-paragraph short stories—commonly referred to as pentigraf—remain uncommon at the elementary level, particularly at SDN 1 Selajambe, Cisaat District, Sukabumi Regency. This study aims to analyze the creative capacity of fifth-grade students in composing pentigraf, with a focus on their cognitive process, language use, and the influence of the learning environment. Employing a qualitative case study method, data were collected through observation, student writing samples, and documentation, involving all 30 students in the class. The findings show that students were able to construct short narratives that reflect intrinsic story elements, cultural dimensions, and social environment influences. Observations also indicate that students were familiar with fundamental narrative components, such as plot structure and character development. The writing process allowed students to sharpen their creativity in forming coherent plots, creating relatable characters, and selecting life-relevant themes. These results affirm that elementary students possess the potential to develop creative literacy through concise narrative forms. The study highlights the pedagogical significance of integrating short-form creative writing to strengthen expressive and imaginative capabilities in early education. Keywords: creativity, primary education, three-paragraph story, pentigraf, narrative literacy